Dissemination of Evacuation Routes for Earthquake and Tsunami Hazards in the Red Zone of Johan Pahlawan District at the Aceh Health Polytechnic - Hilma Erliana; Cut Liliiza Yusra; Lutfi Lutfi; Intan Wulansari; Andi Mustari; Rahmad Nuthihar (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
This community service activity provides information related to disaster and tsunami evacuation routes in the city of Meulaboh, West Aceh Regency, especially in the red zone area. Poltekkes is a vocational college located in Meulaboh, West Aceh District, which is in the red zone area. Communities in the red zone are prone to earthquakes and tsunamis, so they must carry out an evacuation process. The method of implementing this community service activity consists of socializing evacuation routes consisting of 7 routes in Johan Pahlawan District and 5 routes in Meureubo District. Measuring the achievements of socialization activities was carried out by distributing questionnaires to students, including filling in suggestions and input for planning earthquake and tsunami disaster evacuation routes. The results of the questionnaire showed that the Poltekkes students, after the socialization was carried out, already knew the 12 evacuation routes provided. On average, students understand the current condition of the evacuation routes that have been socialized. Students also mostly answered agree from each question given. For questions related to problems encountered during the evacuation process, 63.8% answered that there was congestion at the intersection because each vehicle met from a different direction, 53.2% mixed residents who evacuated with vehicles and people who ran during the evacuation process ongoing, and 29.8% answered that the capacity of the road section exceeded the capacity of the community conducting the evacuation.